The Effect Of Shoot Growth From Single Stick Rejuvination With Clipping Treatment On Branch Growth Of Robusta Coffee (Coffea Canephora L.) BP308 Clone - Hartatie, Dian; Ramadhani, Aditya Dwi; Setyoko, Ujang; Cahyaningrum, Descha Giatri; Dinata, Gallyndra Fatkhu (P3M Politeknik Negeri Jember, 2025)
Robusta coffee (Coffea canephora L.) is the type of coffee most widely developed by farmers in Indonesia. The BP308 is a clone discovered by the coffee and cocoa research center which is included in the Robusta coffee clone which has a large and sturdy stature. One of the coffee plant maintenance activities that needs to be carried out is pruning so that coffee plant productivity can be optimal by removing old branches that are less productive and replacing them with young branches that are more productive. Pruning is a clipping, especially for plants that have difficulty growing reproductive branches. Clipping is carried out at the beginning of the rainy season so as not to stimulate the formation of flowers on the circumcised branches. The method used T-test calculations from the results of rejuvenation of single stems with treatment of one node and two nodes resulting from clipping on shoot growth and the data is then analyzed using a quantitative descriptive analysis method. The results show that there is no influence on shoot length parameters. However, it has a significant increase in the number of leaves from 1,47 to 2,33, and it has a significant increase in shoot diameter from 1,63 mm to 2,38 mm. This is the first study comparing single vs. double node clipping on BP308 clone under specific microclimate conditions.